Congruence and its role in manufacturing strategy: an audit of goals and systems - Neely, Andy (1993)
This thesis is concerned with the realisation of manufacturing strategies. It describes the development and testing of a structured methodology which can be used to determine some of the reasons why a firm may be unable to implement its manufacturing strategy. The methodology is known as a "congruence audit".